Slottet i Transsylvanien - Ladegaard, Jakob (Passage - Tidsskrift for litteratur og kritik, 2011)
Jakob Ladegaard: “The Castle in Transylvania. Gothic Spaces between East and West in Bram Stoker’s Dracula and Franz Kafka’s The Castle” The article investigates the hitherto largely ignored traces of the Gothic literary tradition in Franz Kafka’s novel The Castle (1926) by reading it in continuation of Bram Stoker’s novel Dracula (1897). It is argued that the interpretation of the ghostlike presence of the Gothic vampire in Kafka can yield new insights into the relation between body, space and power in The Castle and his work in general. Inspired by Michel Foucault’s analysis of panoptic spaces and biopower, it is further claimed that Stoker and Kafka, shaped by their respective geopolitical contexts, both use the generic features of the Gothic to reflect – the one mainly affirmatively, the other critically – on larger historical and ideological issues of gender, the modern state apparatus and the relation between Western and Eastern Europe around the turn of the century.